(untitled) (Nordic Journal of Practical Theology, 2024)
This article analyses and discusses funeral participation and participants in funerals in Denmark. Through a data material consisting of survey data, observations and personal interviews, it asks: who participates in funerals, in terms of social background variables and in terms of relations with the deceased? What do participants do in the course of and in relation to the funeral? Which patterns are there between types of participants and patterns of actions? Through engaging theoretical concepts suggested by Bailey and Walter, as well as O’Rourke et al., as well as a practice-theoretical perspective, it suggests that not only are there quite clear patterns in participation and participants actions, but that these are also essential for the pursuit of funerals’ purposes as well as for forming funerals’ subjects. By doing that, it contributes to the so far rather limited research on funeral participation.